Introduction of the day case total laparoscopic hysterectomy (TLH) protocol. (29th July 2022) - Byford, Sally; Madhok, Drishti; Baldan, Paula; Amey, Guy; Barber, James; Harris, Rhys; Walker, Graeme
Abstract : Background: Traditionally total laparoscopic hysterectomy (TLH) patients are admitted for 1–2 days post‐operatively. Day case TLH has been proven to be feasible and safe in other countries; however, this tertiary Queensland hospital is one of the first Australian institutions to introduce a day case TLH protocol. Aim: To pilot the implementation of our day case TLH protocol assessing the feasibility, safety and patient satisfaction of same‐day discharge. Materials and Methods: A retrospective audit of the implementation of our day case TLH protocol at a tertiary Queensland hospital was conducted. Primary outcome was length of post‐operative hospital stay. Secondary outcomes included perioperative complications and post‐operative re‐presentation rates. Patient satisfaction was assessed through a patient questionnaire. Results: Seventy‐seven patients were included in the study. There were 94.81% patients who went home on the same day. Their average length of post‐operative hospital stay was 7.72 (SD ± 3.36) hours. Of the patients who did achieve same‐day discharge, the average length of stay was 7.05 (SD ±1.46) hours. There were no significant differences in perioperative complications or re‐presentation rates compared to previously published literature. Patients reported they were extremely satisfied with day case TLH. Conclusion: The implementation of our day case TLH protocol is feasible, safe and well received by patients in our tertiary Australian hospital. These results can have multimodal effects in healthcare: decrease in hospital costs by reducing length of stay and overnight admissions, improved theatre efficiency and patient flow, while maintaining patient safety and satisfaction.